2009
DOI: 10.1002/app.31109
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of air flow field of the melt blowing slot die via numerical simulation and genetic algorithm

Abstract: The air flow field plays a key role in melt blowing. In this article, an optimal design procedure that improves the airflow field of melt blowing is proposed. A parameter, stagnation temperature which is a combination of static temperature and kinetic temperature, is proposed to evaluate the air flow field. The stagnation temperature is obtained via computer simulation, while optimization is accomplished by genetic algorithm. Four main geometry parameters of the slot die: slot width, nose piece width, slot ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…They found that the velocity and temperature decay were affected by the die geometry significantly. Recently, we11 simulated the air velocity and temperature fields of a melt‐blowing slot die and analyzed the effects of the slot angle, slot width, and nose piece on the air‐flow field.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the velocity and temperature decay were affected by the die geometry significantly. Recently, we11 simulated the air velocity and temperature fields of a melt‐blowing slot die and analyzed the effects of the slot angle, slot width, and nose piece on the air‐flow field.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the relatively long computational time in these applications. Other applications include heat exchange performance [71e73], airfoil design [74,75], car shape design [76], airflow field optimization of a melt blowing slot die [77], and geometric optimization of a gas turbine transition piece [78].…”
Section: Cfd-based Genetic Algorithm Methodsmentioning
confidence: 99%
“…In our research group, we have been involved with extensive studies of various aspects of melt blowing process, including, fiber formation model , airflow field , and melt blown web formation . We developed a bead‐viscoelastic element fiber model and then adopted a mixed Euler‐Lagrange approach to simulate the three‐dimensional fiber motion, especially the whipping motion in the process of melt blowing.…”
Section: Introductionmentioning
confidence: 99%